An adaptable mesocosm platform for performing integrated assessments of nanomaterial risk in complex environmental systems - Auffan, Mélanie (Nature Publishing Group, 2014)
Physical-chemists, (micro)biologists, and ecologists need to conduct meaningful experiments to study the environmental risk of engineered nanomaterials with access to relevant mechanistic data across several spatial and temporal scales. Indoor aquatic mesocosms (60L) that can be tailored to virtually mimic any ecosystem appear as a particularly well-suited device. Here, this concept is illustrated by a pilot study aimed at assessing the distribution of a CeO2-based nanomaterial within our system at low concentration (1.5 mg/L). Physico-chemical as well as microbiological parameters took two weeks to equilibrate. These parameters were found to be reproducible across the 9-mesocosm setup over a 45-day period of time. Recovery mass balances of 115 ± 18% and 60 ± 30% of the Ce were obtained for the pulse dosing and the chronic dosing, respectively. This demonstrated the relevance of our experimental approach that allows for adequately monitoring the fate and impact of a given nanomaterial.